Impact of incubation period on biodegradation of petroleum hydrocarbons from refinery wastewater in Kuantan, Malaysia by indigenous bacteria - Ibrahim, Muna; Makky, Essam A.; Nina Suhaity, Azmi; Jamil, Ismail (Springer, 2018)
This work studied the biodegradation of petroleum hydrocarbons (PHCs) extracted from refinery wastewater to produce industrially important by-products at different incubation periods. Two out of 13 bacterial isolates, KRD2 and KRA4 were isolated. Dichloromethane was used to extract the PHC, and gas chromatography-mass spectrometry (GC-MS) analysis revealed that the refinery wastewater PHC was successfully biodegraded using the selected bacterial isolates within 15 days of incubation. Both KRD2 and KRA4 isolates degraded all 13 initially extracted PHC compounds within 5 days, except C13BD and C9BD, which produced 6 and 4 compounds as secondary metabolites with peak area percentages of 1.58, 1.38, 0.85, 29.94, 7.59, and 11.16% and 3.55, 2.88, 52.31, and 6.14%, respectively. These metabolites have been reported in industrial and medical applications. After 10 days, only 6 and 8 compounds were degraded by both isolates, respectively, and C11PAD compound was produced, as well as C5PAD, C7PAD, and C13PAD. After 15 days, it was clear that all the initial PHC compounds have been completely degraded by both isolates. Metabolites C5PAD, C6PAD, C8PAD, and C13PAD were produced by KRD2, and metabolites C5PAD, C6PAD, C8PAD, and C9PAD were produced by KRA4 at different peak areas. The alignment revealed that the KRA4 isolate was included in the genus Chryseobacterium gambrini, while KRD2 isolate was successfully identified as Mycobacterium confluentis using the Biolog microbial identification system. The incubation period evidently affected biodegradation process by indigenous degraders. These effective bacteria were shown to be of great potential for further application in biodegradation technology of PHC contaminated refinery wastewater to produce industrially important by-products.